Risk of Depression after Venous Thromboembolism in Patients with Hematological Cancer: A Population-Based Cohort Study - Steiner, Daniel; Horváth-Puhó, Erzsébet; Jørgensen, Helle; Laugesen, Kristina; Ay, Cihan; Sørensen, Henrik Toft (Thrombosis and Haemostasis, 2024)
Background Venous thromboembolism (VTE) may complicate the clinical course of cancer patients and add to their psychological burden.Objectives We aimed to investigate the association between VTE and risk of subsequent depression in patients with hematological cancer.Patients and Methods We conducted a population-based cohort study using Danish national health registries. Between 1995 and 2020, we identified 1,190 patients with hematological cancer and incident VTE diagnosed within 6 months before to 1 year after cancer diagnosis. A comparison cohort of patients with hematological cancer without VTE (n = 5,325) was matched by sex, year of birth, cancer type, and year of cancer diagnosis. Patients were followed until diagnosis of depression, emigration, death, study end (2021), or for a maximum of 3 years. Depression was defined as hospital discharge diagnosis of depression or ≥1 prescription for antidepressants. Absolute risks of depression were computed with cumulative incidence functions, treating death as competing event. Hazard ratios (HRs) with 95% confidence intervals (CIs) were computed using Cox proportional hazards regression models, adjusting for comorbidities.Results Depression was observed in 158 hematological cancer patients with and 585 without VTE. The 3-year absolute risks of depression were 13.3% (95% CI: 11.5–15.3%) in the VTE cancer cohort and 11.1% (95% CI: 10.3–12.0%) in the comparison cancer cohort, corresponding to a risk difference of 2.2% (95% CI: -1.8–6.5%). VTE was associated with an increased relative risk of depression (adjusted HR: 1.56, 95% CI: 1.28–1.90).Conclusion VTE was associated with an elevated risk of subsequent depression in patients with hematological cancer.
Keywords: epidemiology; hematological cancer; neoplasms; disorders; venous thromboembolism